Flutningstími og gæði meðferðar hjá sjúklingum með ST-hækkunar hjartadrep á Norður- og Austurlandi - Þórir Svavar Sigmundsson; Björn Gunnarsson; Sigurður Benediktsson; Gunnar Þór Gunnarsson; Sveinbjörn Dúason; Gestur Þorgeirsson (Læknafélag Íslands, Læknafélag Reykjavíkur, 2010)
Neðst á síðunni er hægt að nálgast greinina í heild sinni með því að smella á hlekkinn Skoða/Opna(view/open) INTRODUCTION: A good outcome of patients presenting with STEMI (ST-Segment Elevation Myocardial Infarction) depends on early restoration of coronary blood flow. Pre-hospital fibrinolysis is recommended if primary percutaneous coronary intervention (PPCI) cannot be performed within 90 minutes of first medical contact (FMC). The purpose of this study was to study transport times for patients with STEMI who were transported with air-ambulance from the northern rural areas of Iceland to Landspitali University Hospital in Reykjavík, and to assess if the medical management was in accordance with clinical guidelines. MATERIALS AND METHODS: Retrospective chart review identified 33 patients with STEMI who were transported with air-ambulance to Landspitali University Hospital in Reykjavík during the years 2007 and 2008. RESULTS: The total time from first medical contact to arrival at Landspitali University Hospital emergency room was 3 hours and 7 minutes (median). All patients received aspirin and 26 (78.8%) received clopidogrel and enoxaparin. 16 patients (48.5%) received thrombolytic therapy in median 33 minutes after FMC and 15 patients had PPCI performed in median 4 hours and 15 minutes after FMC. Estimated PCI related delay was 3 hours and 42 minutes (median). One patient died and one was resuscitated within 30 hospital days. Mean hospital stay was 6.0 days. CONCLUSIONS: First medical contact to balloon time of less than 90 minutes is impossible for patients with STEMI transported from the northern rural areas to Landspitali University Hospital in Reykjavík. Medical therapy was in many cases suboptimal and PCI related delay too long. Inngangur:Horfur sjúklinga með brátt ST-hækkunar hjartadrep ráðast af því hversu lengi kransæð er lokuð. Ef kransæðavíkkun verður ekki viðkomið innan 90 mínútna frá komu til læknis er réttast að veita meðferð með segaleysandi lyfi. Tilgangur þessarar rannsóknar var að kanna ...